Bronze Matrix with Hebrew Inscription (Proceedings of the Society of Antiquaries of Scotland, 1852)
Dr. Daniel Wilson presented the matrix of a round seal, whose inscription bore striking resemblances to those displayed in the engravings of a vol of the Gentlemen's Magazine from June 1787. The figure is a turbaned head, and the words in Hebrew letters. Dr. Wilson then relayed the opinions of several scholars on the reading of the inscription. Beyond the mention of a Solomon son of Isaac, the experts can find few specifics to agree on.